(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the current state of agricultural production, inadequate technical security of rural producers, analyzed the development of technical equipment of rural enterprises, made a calculation of the required composition of technical base of agricultural production by applying a regression equation on the imputation principle of optimization of structure of technical resources. Also in the ways of the agroservice enterprises, where the concentration of modern machines used to perform time-consuming and responsible work that is not able to carry out individual farms.